The Influence of Work Motivation and Work Discipline on Employee Performance at Daffa Florist - Nurhanifa Salsabilla Alista; Anton Budi Santoso (Equivalent: Jurnal Ilmiah Sosial Teknik, 2024)
The purpose of this study was to determine the effect of Work Motivation and Work Discipline on Employee Performance at Daffa Florist. For the method used in this research is to use quantitative methods using survey methods through questionnaires distributed to employees. Especially those who served at Daffa Florist involving 28 employees. The data analysis techniques used in this study are validity and reliability tests, descriptive analysis, classical assumption tests, multiple linear regression tests and hypothesis testing. The result of this research is to find out how the influence of Work Motivation and Work Discipline on Employee Performance at Daffa Florist, so this study uses the data analysis techniques mentioned to find out how employee performance and its influence on employee work motivation. Data analysis was carried out with the help of the SPSS 25 (Stastistic Product And Service Solution) application program, with the help of the program it showed the results that the probability in the influence of work motivation with the calculation of the formula based on the application program was 0.017%, in order to better know the results of the comparison between work motivation and work discipline, the calculation was carried out again using the Microsoft Excel program with the results of 1.986%. So that the results of the probability calculation show that the calculation of the comparison between the effect of Work Motivation and Work Discipline on Employee Performance at Daffa Florist is 0.000 <0.05%.